MODEL PEMBELAJARAN KREATIF DAN PRODUKTIF BERBASIS MASALAH KONTEKSTUAL MELALUI KEGIATAN LESSON STUDY UNTUK MENINGKATAN KREATIVITAS EKSPRESI TULIS PUISI - Lalu Fakihuddin (MABASAN, 2017)
The purposes of the research are (1) to increase the activity of student in writing poem byapplying creative and productive studying model through Lesson Study activities; and (2) toincrease the quality of expressive poetry writing process through Lesson Study activities. Inorder to achieve the goals, Lesson Study includes planning, executing, and observing. Theall three stages have been done in four time/cycles in the Lesson Study lectures. Lecturesand every cycle (1 to 4), had been focused on expressive modern poetry writing based ontopic such as private name, disastrous event, beauty of nature, social events/problem, andpolitical problem. Every part of study has been presented/done in creative and productivestudying model which is based on fundamental principles of creative and productivelearning such as orientation, exploration, interpretation, and re-creation. The result of thisresearch are (1) implementation of creative and productive studying model based oncontextual problem through Lesson Study activity in creative literature writing, especiallymodern poetry writing can increase the creativity of students, (2) creative and productivestudying model through Lesson Study activity can increase quality of creative literaturewriting subject . It can be seen from the increasing in liveliness, self-service andcooperation and motivation of the student in solving tasks that had been assigned in thestudy. It is noteworthy that students also think that this method is interesting and enjoyable.